PENGUKURAN KONVERGEN UNTUK MENILAI KESTABILAN LUBANG BUKAAN BAWAH TANAH DI TAMBANG EMAS CIKIDANG - Wedhanto , Sonny
Cikidang gold mine applies Underhand Stuffed Stoping system that creates vertical underground opening. Stability factor and outside factors influencing stability need to be found. Evaluation was carried out by convergence measurement from the opposite walls of the opening by using a convergence-meter. The observation was carried out at eight locations; two locations at Hill-1, and three locations each at Hill-2 and Hill-3. Stability evaluation used rate of displacement method from Zhenxiang (1984). The result of the evaluation are: 1) Hill-2 experienced the greatest displacement, in 697 hours the distance between the walls decreased by 28,39 mm. Hill-1 experienced the smallest displacement, in 702,25 hours the distance between the walls decreased by 4,76 mm. 2) The opening in Hill-1 is stable, the opening in Hill-2 is relatively stable, and the opening in Hill-3 is relatively stable to stable. 3) Outside factors increasing the rate of displacement are: earthquake, explesion up to 8,5-9 m above observation point, and exavation of the face up to 11,60-15,50 m in front of the observation point.